Gender, Land, and Place: Considering Gender within Land-Based and Place-Based Learning - Spillett, Tasha (Journal for the Study of Religion, Nature and Culture, 2021)
Considering how gender operates within land-based and place-based learning is critical as both human and more-than-human relations and relationships have been heavily shaped and regulated by settler colonialism and settler heteropatriarchy. The deterioration of Indigenous notions of gender and the forceful colonial imposition of a Western gender binary has served to fracture Indigenous peoples’ relationships with Land.